Scheduling Copper Refining and Casting Operations by Means of Heuristics for the Flexible Flow Shop Problem - Parada-Daza, V (2011)
Management of the operations in a copper smelter is fundamental for optimizing the use of the plant s installed capacity. In the refining and casting stage, the operations are particularly complex due to the metallurgical characteristics of the process. This paper tackles the problem of automatic scheduling of operations in the refining and casting stage of a copper concentrate smelter. The problem is transformed into a flexible flow shop problem and to solve it, an iterative method is proposed that operates in two stages: in the first stage, a sequence of jobs is constructed that configures the lots, and in the second, the constructed solution is improved by means of simulated annealing. Fifteen test problems are used to show that the proposed algorithm improves the makespan by an average of 9.42% and the mean flow time by 12.19% with respect to an existing constructive heuristic. © 2011 Bralizian Operations Research Society.